SARS-CoV-2 prevalence and immunity: a hospital-based study from Malawi. (March 2022) - Meinus, C.; Singer, R.; Nandi, B.; Jagot, O.; Becker-Ziaja, B.; Karo, B.; Mvula, B.; Jansen, A.; Baumann, J.; Schultz, A.
Highlights: Early-stage, large-scale SARS-CoV-2 serosurvey combining PCR and sVNT in Africa SARS-CoV-2 prevalence and immunity is grossly underestimated by official surveillance Asymptomatic and subclinical infection and transmission are high targeted risk group approach preferable over undirected lockdown measures Conduction of sVNT is feasible even with limited laboratory infrastructure Abstract: Background: COVID-19 transmission and disease dynamics in sub-Saharan Africa are not well understood. Our study aims to provide insight into COVID-19 epidemiology in Malawi by estimating SARS-CoV-2 prevalence and immunity after SARS-CoV-2 infection in a hospital-based setting. Methods: We conducted a hospital-based, convenience sampling, cross-sectional survey for SARS-CoV-2 in Lilongwe, Malawi. Participants answered a questionnaire and were tested for SARS-CoV-2 by enzyme-linked immunosorbent assay and real-time reverse-transcription polymerase chain reaction (RT-PCR). A surrogate virus neutralization test (sVNT) was performed in seropositive samples to estimate immunity. Poisson regression was used to assess SARS-CoV-2 point prevalence association with demographic and behavioral variables. Findings: The study included 930 participants. We found a combined point prevalence of 10.1%. Separately analyzed, RT-PCR positivity was 2.0%, and seropositivity was 9.3%. Of tested seropositive samples, 90.1% were sVNT positive. We found a high rate (45.7%) of asymptomatic SARS-CoV-2 infection. SARS-CoV-2 point prevalence was significantly associated with being a healthcare worker. Interpretation: Our study suggests that official data underestimate COVID-19 transmission. Using sVNTs to estimate immunity in Malawi is feasible and revealed considerable post-infection immunity in our cohort. Subclinical infection and transmission are probably a game-changer in surveillance, mitigation and vaccination strategies.